2020
DOI: 10.3390/jcm9061638
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Mitochondrial Efficiency and DNA Oxidation in Human Sperm after In Vitro Myo-Inositol Treatment

Abstract: Semen samples are known to contain abnormal amounts of reactive oxygen species (ROS) and oxygen free radicals; therefore, the identification of antioxidant molecules able to counteract the oxidative damage caused by ROS is foresight. Indeed, improving semen quality in terms of motility and reduction in DNA damage, can significantly improve the fertilization potential of sperm in vitro. To this regard, myo-inositol, based on its antioxidant properties, has been reported to be effective in improving sperm qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…For instance, increased ROS production causes DNA fragmentation or lipid peroxidation, which compromises the membrane and impairs mitochondrial activity [ 53 , 54 ]. In fact, antioxidants have been proposed as adjuvants for sperm culture medium, being beneficial for spermatozoa viability and motility maintenance [ 55 , 56 , 57 ]. Since increased ROS production can lead to oxidative stress-induced damage, we also analyzed lipid peroxidation, protein oxidation, and protein nitration.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increased ROS production causes DNA fragmentation or lipid peroxidation, which compromises the membrane and impairs mitochondrial activity [ 53 , 54 ]. In fact, antioxidants have been proposed as adjuvants for sperm culture medium, being beneficial for spermatozoa viability and motility maintenance [ 55 , 56 , 57 ]. Since increased ROS production can lead to oxidative stress-induced damage, we also analyzed lipid peroxidation, protein oxidation, and protein nitration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers decided to evaluate 8-OHdG, one of the first products of oxidative damage to DNA. The samples treated with MI displayed reduced levels of 8-OHdG [153]. Therefore, MI can improve the sperm parameters related to the quality and in vitro fertilization process.…”
Section: Mi: In Vitro Studiesmentioning
confidence: 91%
“…In addition, it has been determined that inositol increases mitochondrial calcium levels, improves sperm mitochondrial function with an antioxidative effect and prevents apoptosis [ 32 ]. Governin et al [ 54 ] demonstrated the ability to prevent oxidation damage in DNA with 20 mg/mL MI, with a significant decrease in the level of 8-OHdG in sperm. It has been shown in different studies that the antioxidant properties of inositol on sperm quality, oxidant and antioxidant levels and DNA damage, when added before cryo-storage, differ according to the type of animal used.…”
Section: Introductionmentioning
confidence: 99%